Early Changes in [18F]FDG Uptake as a Readout for PI3K/Akt/mTOR Targeted Drugs in HER-2-Positive Cancer Xenografts. (25th May 2021) - Dockx, Yanina; Vangestel, Christel; Van den Wyngaert, Tim; Huizing, Manon; De Bruycker, Sven; Pauwels, Patrick; Staelens, Steven; Stroobants, Sigrid
Abstract : We investigated the potential use of [ 18 F]FDG PET as a response biomarker for PI3K pathway targeting therapies in two HER-2-overexpressing cancer models. Methods . CD-1 nude mice were inoculated with HER-2-overexpressing JIMT1 (trastuzumab-resistant) or SKOV3 (trastuzumab-sensitive) human cancer cells. Animals were treated with trastuzumab, everolimus (mTOR inhibitor), PIK90 (PI3K inhibitor), saline, or combination therapy. [ 18 F]FDG scans were performed at baseline, two, and seven days after the start of the therapy. Tumors were delineated on CT images and relative tumor volumes (RTV) and maximum standardized uptake value (SUVmax ) were calculated. Levels of pS6 and pAkt on protein tumor lysates were determined with ELISA. Results . In the SKOV3 xenografts, all treatment schedules resulted in a gradual decrease in RTV and delta SUVmax ( Δ SUVmax ). For all treatments combined, Δ SUVmax after 2 days was predictive for RTV after 7 days (r = 0.69, p = 0.030 ). In JIMT1 tumors, monotherapy with everolimus or PIK90 resulted in a decrease in RTV (− 30 % ± 10 % and − 20 % ± 20 %, respectively) and Δ SUVmax (− 39 % ± 36 % and − 42 % ± 8 %, respectively) after 7 days of treatment, but not earlier, while trastuzumab resulted in nonsignificant increases compared to control. Combination therapies resulted in RTV and Δ SUVmax decrease already at day 2, except for trastuzumab+everolimus, where an early flare was observed. For all treatments combined, Δ SUVmax after 2 days was predictive for RTV after 7 days (r = 0.48, p = 0.028 ), but the correlation could be improved when combination with everolimus (r = 0.59, p = 0.023 ) or trastuzumab (r = 0.69, p = 0.015 ) was excluded. Conclusion . Reduction in [ 18 F]FDG after 2 days correlated with tumor volume changes after 7 days of treatment and confirms the use of [ 18 F]FDG PET as an early response biomarker. Treatment response can however be underestimated in schedules containing trastuzumab or everolimus due to temporary increased [ 18 F]FDG uptake secondary to negative feedback loop and crosstalk between different pathways.